High pressure pure- and mixed-gas separation of CO2/CH4 by thermally-rearranged and carbon molecular sieve membranes derived from a polyimide of intrinsic microporosity - Swaidan, Raja; Ma, Xiaohua; Litwiller, Eric; Pinnau, Ingo (Journal of membrane science, 2013)
Natural gas sweetening, one of the most promising venues for the growth of the membrane gas separation industry, is dominated by polymeric materials with relatively low permeabilities and moderate selectivities. One strategy towards improving the gas transport properties of a polymer is enhancement of microporosity either by design of polymers of intrinsic microporosity (PIMs) or by thermal treatment of polymeric precursors. For the first time, the mixed-gas CO2/CH4 transport properties are investigated for a complete series of thermally-rearranged (TR) (440°C) and carbon molecular sieve (CMS) membranes (600, 630 and 800°C) derived from a polyimide of intrinsic microporosity (PIM-6FDA-OH). The pressure dependence of permeability and selectivity is reported up to 30bar for 1:1, CO2:CH4 mixed-gas feeds at 35°C. The TR membrane exhibited ~15% higher CO2/CH4 selectivity relative to pure-gas feeds due to reductions in mixed-gas CH4 permeability reaching 27% at 30bar. This is attributed to increased hindrance of CH4 transport by co-permeation of CO2. Interestingly, unusual increases in mixed-gas CH4 permeabilities relative to pure-gas values were observed for the CMS membranes, resulting in up to 50% losses in mixed-gas selectivity over the applied pressure range. [Display omitted] . •TR polymers show more stable mixed-gas CO2/CH4 selectivity than CMS membranes.•TR: 15% increase in αMixCO2/CH4 over pure-gas values up to 30bar.•TR: 27% reduction in PMixCH4 due to co-permeation of CO2 at 30bar.•CMS membranes retain higher selectivity than TR membranes up to 30bar.•CMS: 50% loss in αMixCO2/CH4 and increase in PMixCH4 over pure-gas values.